2014 XXXIth URSI General Assembly and Scientific Symposium (URSI GASS) 2014
DOI: 10.1109/ursigass.2014.6930131
|View full text |Cite
|
Sign up to set email alerts
|

SVM-based classification of breast tumour phantoms using a UWB radar prototype system

Abstract: In this paper, a follow-up study exploring the classification of phantoms mimicking benign and malignant breast tumours, using a pre-clinical Ultra Wideband (UWB) prototype imaging system, is presented. A database of 13 benign and 13 malignant tumour phantoms was created using material which mimicked the dielectric properties of tumour tissues in the 1-6GHz frequency range. The classification was performed using a machine learning algorithm -Support Vector Machines (SVM) -and the results were compared to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Benign tumours are roughly elliptical and usually have well circumscribed margins, and malignant tumours have irregular shapes and are surrounded by a radiating pattern of spikes, commonly referred to as spicules [ 22 , 23 , 24 , 25 , 26 ]. Previous studies have already shown how microwave backscattered signals may change if tumours of different sizes or shapes are present within the breast [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. These studies have also demonstrated that classification and machine learning algorithms are able to learn from the shape differences in backscattered signals, albeit in relatively simple datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign tumours are roughly elliptical and usually have well circumscribed margins, and malignant tumours have irregular shapes and are surrounded by a radiating pattern of spikes, commonly referred to as spicules [ 22 , 23 , 24 , 25 , 26 ]. Previous studies have already shown how microwave backscattered signals may change if tumours of different sizes or shapes are present within the breast [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. These studies have also demonstrated that classification and machine learning algorithms are able to learn from the shape differences in backscattered signals, albeit in relatively simple datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental datasets have also been used to assess the performance of diagnosis systems, namely by using principal component analysis in combination with support vector machines, linear discriminant analysis and quadratic discriminant analysis. In [ 36 , 37 ], tumour phantoms with various sizes and shapes were immersed in a breast phantom with dielectric properties matching those of adipose tissue. Importantly, the experimental results presented in these studies are in general agreement with previous numerical data.…”
Section: Introductionmentioning
confidence: 99%
“…The latter three classifiers -NB, DT, and kNNwere used to assess all signals, expanding and complementing prior studies. 25,26 These classifiers are well-suited to analyse data such as those collected in this study: continuous time domain signals with labeled data. For example, NB is based on probabilities, DT is based on decision analysis and kNN is based on pattern recognition.…”
Section: B3 Classification Algorithmsmentioning
confidence: 99%
“…To the best of our knowledge, this was the first study to report experimental results using a MWI prototype system for tumor classification based on tumor shape. The study was later expanded to include SVM as a classification algorithm which, despite the good accuracy results, required high computational power in order to provide an efficient hyperparameters optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical trials were performed by several groups Meaney et al, 2000;Porter et al, 2016), problems-such as the difference between the dielectric properties between tumor and glandular tissues being less than that in the existing data (Bourqui, Garrett, et al, 2012;J. Garrett & Fear, 2014; J. D. Garrett & Fear, 2015;Winters et al, 2006) and classification-remain (Conceição et al, 2014;McGinley et al, 2010;O'Halloran et al, 2011;O'Loughlin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%